A leitura da Bíblia na perspectiva de João Calvino: uma introdução à hermenêutica calvinista a partir dos salmos de lamento - Sifoleli, Israel (2007)
In this work the author looks for to rescue the reading that Calvin made of the Psalms of lament. It has as intention to present an introduction to the Calvin s hermeneutics. It calls attention for the fact of that although the great contribution of Calvin, its hermeneutics still is, in many aspects, stranger in Brazil. The author makes an attempt to establish the influences on Calvin s thought that had contributed for his hermeneutics. It continues demonstrating the importance of the authority of the Bible for Calvin. After that he presents the main points of Calvin s hermeneutics and for a better understanding, he divides them in presuppositions, principles and approaches. In the last chapter the focus is in an analysis of Calvin s hermeneutics, having the modern study of Psalms as aid. Finally, it presents an attempt of dialogue between Calvin s hermeneutics and contemporary Brazilian Protestantism. This dialogue is presented in the form of some challenges.